The Role Of Green Hydrogen In Achieving Sustainable Development - Kadari, Ahmed; Tayeb, Saida (جامعة الوادي University of Eloued, 2024)
This research paper explores the contribution of green hydrogen to achieving sustainable development. Produced from renewable energy sources, green hydrogen offers a promising pathway for decarbonizing various sectors. The paper examines its potential to enhance the environmental, economic, and social dimensions of sustainability. It focuses on the production processes of green hydrogen, its applications, and the associated challenges and opportunities for its adoption. Green hydrogen is generated through the electrolysis of water, making it a clean alternative to fossil fuels. This technology converts renewable energy into hydrogen, which can be utilized for energy storage and transportation. Its role in sustainable development is significant as it helps reduce carbon emissions and supports the transition to a low-carbon economy. By integrating green hydrogen into energy systems, countries can effectively address climate change challenges and enhance energy security, aligning with global sustainability goals and contributing to long-term environmental and economic benefits.
Keywords: Green; Hydrogen; Green Hydrogen; Sustainable Development; Renewable Energy